Pengembangan Media Pembelajaran Berbasis Android Menggunakan Smart Apps Creator Pada Materi Bangun Ruang Sisi Datar di Kelas VIII SMP Negeri 2 Amabi Oefeto - Hello, Risky Arnis Septian (Universitas Nusa Cendana, 2023)
This study aims to develop android-based mathematics learning media using Smart Apps Creator on flat-sided space building material for class VIII students of SMP Negeri 2 Amabi Oefeto which is valid, practical, and effective. The method used in this research is the Research and Development method with the ADDIE model, namely: analysis, design, development, implementation, and evaluation. The data collection techniques and instruments used were interviews, questionnaires, and tests. The results showed that the average validity of the media was 4.5 including the